ANALISIS STRATEGI BLUE OCEAN “CHINA CONSTRUCTION BANK INDONESIA” - Witjaksono, Cindy Julian (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
This research aims to analyze the blue ocean strategy of the Company "China Construction Bank Indonesia". Following the "market oriented, customer-centric" business concept, Bank CCB Indonesia is committed to developing itself into a world-class banking group. Existing strategies will be further developed so they can compete in new markets. The method in this research uses surveys and literature studies to understand, research and learn about the strategies used by Bank CCB Indonesia. To reconstruct the elements of Bank CCB Indonesia to enter a new value curve, researchers developed a strategy using several analytical tools, namely The Four Action Framework and The ERRC Grid. The research results show that the blue ocean strategy can increase service user satisfaction, create new market segments, and provide completeness for products and services from Bank CCB Indonesia. Implementation of the strategy will provide positive benefits for banking services businesses to be more competitive in new markets and become a sustainable business. Therefore, it is hoped that this research can contribute to the understanding and application of the blue ocean strategy in banking services in Indonesia. Apart from that, it can contribute to the development of marketing strategies in the face of intense competition in the banking industry. Keywords: strategy, banking, blue ocean strategy, new markets.